Pengaruh Inflasi, Suku Bunga dan Nilai Tukar Terhadap Profitabilitas Perbankan Syariah - Khusnul Khotimah; Muhammad Imam Masyari; Muhammad Nur Adila Hikam; Muhammad Taufiq Abadi (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The purpose of writing this research is to determine the effect of interest rate inflation and exchange rates on the profitability of sharia banking. The method used in this research is literature, namely by collecting data by looking for sources from various sources such as books, journals, articles that are appropriate to the topic of discussion. Banks are business entities that collect funds from the public in the form of savings and distribute them to the public in the form of credit and/or other forms in order to improve the standard of living of many people, one of the ratios that can measure banking performance is the profitability ratio with indicators including Return On Assets.